Literatura nas periferias: estudo antropológico sobre produções literárias na zona sul de São Paulo - Toledo, Sarah Ferreira de [UNIFESP] (2014)
This research is intended to understand the relationship between the context and the discourse existing in literary productions created by writers from the south region of São Paulo. The productions are directly related to the saraus, which have been propagated to the city suburbs since thirteen years ago. These events are articulated by different segments of the society by demands beyond of the literary and artistic issue, including also social and political subjects. This document is focused in the south region because of it is the place from which this cultural movement begin; as well as literature, which is a significant source for understanding the context from a local viewpoint